Global Leaders in Development: a global leadership module across three international pharmacy schools. (5th May 2020) - Steeb, David R.; Bruno‐Tome, Andreia; Pyzik, Oksana; Dascanio, Sarah A.; Bates, Ian
Abstract: Objectives: The objective of this study was to assess the impact of the Global Leaders in Development (GLIDE) module to determine whether the concepts of global mindset, citizenship and leadership can be effectively taught within a short‐term didactic module. Methods: Faculty members of PharmAlliance, a partnership between three schools of pharmacy, created a three‐week optional, non‐credit‐bearing distance‐based global leadership development module. Material and assignments focused on the concepts of global mindset, global citizenship and global leadership as applied to the global health issues of non‐communicable diseases, universal health coverage and primary care. Student self‐rated growth was measured with an adapted fifteen question pre–post‐survey that also included open‐ended questions. Key Findings: Most statements showed growth on the pre–post‐survey with seven being statistically significant ( P  < 0.05). The largest growth involved students' perceived potential to be a global leader in pharmacy (global leadership category), the students' connectedness to the pharmacy profession worldwide (global citizenship category) and the students' awareness of global challenges faced in the pharmacy profession (global mindset category). Qualitative analysis identified several themes for each of the open‐ended questions. Student expectations focused on the desire to expand their global mindset, better understand global pharmacy practice, develop teamwork skills and understand global pharmacy challenges and strategies for engagement. Conclusions: The concepts of global mindset, global citizenship and global leadership may help promote awareness of global health challenges, opportunities to make a global difference in a local context and connectivity to the profession on a global scale.